2018
DOI: 10.3329/jssmc.v8i2.37241
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Pattern In Hypertensive Patients In A Tertiary Care Teaching Hospital, Dhaka, Bangladesh

Abstract: Background: Irrational drug prescribing is a common practice globally; it results in increased morbidity, mortality & economic burden on society. Drug utilization studies are an important tool to promote rational prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
2
0
0
Order By: Relevance
“…In this study, the average age of the patients was 53.6 (±10.8) years. 15 This finding was similar to a study in another tertiary care hospital in Bangladesh. It was comparatively lower than in other studies; Kim et al from Korea reported an average age of 61±11 years, and Yu et al from China reported an average age of 62.3±13.6 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the average age of the patients was 53.6 (±10.8) years. 15 This finding was similar to a study in another tertiary care hospital in Bangladesh. It was comparatively lower than in other studies; Kim et al from Korea reported an average age of 61±11 years, and Yu et al from China reported an average age of 62.3±13.6 years.…”
Section: Discussionsupporting
confidence: 89%
“…Most commonly used antihypertensive medications were angiotensin Receptor blockers or ACE inhibitors, similar to other studies conducted in Bangladesh and other countries. 15,16 A relatively large proportion of patients had several cardiovascular comorbidities, including diabetes mellitus, coronary artery disease, and cerebrovascular disease, similar to the study of Kim et al 16 The present study reported a prevalence of 8.2% for significant sIAD (≥10 mmHg). In terms of systolic inter-arm difference (sAID), 27.3% of patients had sAID <10 mmHg to ≥5 mmHg, and the majority (64.5%) had sAID <5 mmHg.…”
Section: Discussionsupporting
confidence: 88%